Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa SMAN 11 Maros - Wahidatul Munandar; Andi Gunawan Azis; Nur Alamsyah; Anin Asnidar (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Student learning outcomes are the output of the teaching and learning process. One of the problems in learning at school is the low student learning outcomes. This can be known from the initial data on the value of the diagnostic analysis results. Many factors influence learning outcomes, one of which is the learning model. The Problem Based Learning Model is an innovative learning model that requires students to be active and motivate students so that they can support and help each other in mastering the subject matter being studied. Research procedures include the observation stage, preparation stage, implementation stage and evaluation stage. The population and sample in this research were 28 students of class XI MIPA 1 SMAN 11 MAROS. The sampling technique in this research used a saturated sampling technique.